Preventing alcohol-exposed pregnancies among Hispanic women. Issue 1 (2nd January 2017) - Letourneau, Brian; Sobell, Linda Carter; Sobell, Mark B.; Johnson, Kenneth; Heinecke, Nicholas; Robinson, Sean M.
ABSTRACT: Project Healthy CHOICES, a self-administered, mail-based prevention intervention, was developed for women at risk of an alcohol-exposed pregnancy (AEP). Participants were sent their assessment and study materials through the United States Postal Service. This article uses data from a larger study ( N = 354) and focuses on the 89 women who identified as Hispanic. Potential participants who called in response to English and Spanish ads and who said they could read and write Spanish were given a choice of receiving the intervention materials in English or Spanish. The main objective of the present study was to evaluate differences in outcomes as a function of (a) the language in which the intervention materials were received, and (b) the participants' acculturation levels. Prior to the study, all women were at risk of an AEP. At the 6-month follow-up, two thirds (66%) of all Hispanic women had reduced their overall risk of an AEP, primarily by practicing effective birth control. These outcomes are similar to those reported for previous Project CHOICES studies. Significantly more women who requested the intervention materials in English (75%) compared to Spanish (41%) reduced their overall risk of an AEP. Women with high English cultural domain scores were at significantly less risk of an AEP due to effective contraception and a reduced overall risk of an AEP. Compared to other Project CHOICES studies, Project Healthy CHOICES is less intensive; it is self-administered, freely available, and can be completed without visiting a health care practitioner or clinic.